Beyond the Extremism of Radical Muslim Groups: A Socio-Historical Study - Khomaini, Mokhamad Iqbal (Universitas Islam Negeri Raden Mas Said Surakarta, 2017)
Muslim terrorist group is a contrast issue, they are the one who openly opposes the U.S. Oppression, but on another side, they are blamed for being a terrorist. The story started with oppression on Muslim countries everywhere: Afghanistan was invaded by USSR army, then 1991, Iraq also was attacked as a response call from the US to Kuwaiti aid request, then in 2001, Afghanistan was invaded and occupied by the U.S., then the raid over Taliban and all its organization in Pakistan and Afghanistan, the military operation in Iraq, 2003, and daily killing upon Palestinian since 1967 with no ending etc. So, the counter upon oppression rises, but unfortunately those who struggled to defend Muslim territories against U.S. invasion are called as a terrorist. Once upon a time in 2000, Bali was the most destined of tourism but unexpectedly, a big tragedy happened in Indonesia with the bomb explosion in Bali Island and killed 202 people, most of the victims were foreign tourists. The result of investigations pointed to Jemaah Islamiyah as an actor of that incident. The national and International news media posted that Jamaah Islamiyah did a terror on the basis of jihad against America and its allies who invaded a Muslim country, but unfortunately, the victims were civilians who have nonsense affiliated with politics.